Pengaruh pad, dau, dak terhadap ipm dengan belanja modal sebagai variabel intervening (studi pada kabupaten/kota di provinsi papua tahun 2009 -2013) - Raviyanti, Ayu Aldi; Rahayu, Sri; Mahardika, Dewa Putra Krishna (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
One way to measure the success or performance of a country or region in the field of human development used the Human Development Index (HDI). Human Development Index (HDI) is a composite index to measure the achievement of human development based on a number of basic components of quality of life. The purpose of this study is to determine how much Local Genuine Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Human Index Development (HDI) and Capital Expenditure in the Regencies/Cities of Papua Provinci for years 2009-2013, as well as determine the influence of PAD, DAU and DAK to HDI with Capital Expenditure as an intervening variable either simultaneously or partially. The method that used in this research is panel data regression using Random Effect Model (REM) with research period of year 2009-2013 using software Eviews 8.0. Total population in this research were 29 regencies/cities. By using purposive sampling, obtained sample of 24 regencies/cities. The results of this study indicate that PAD, DAU, and DAK jointly is influenced on Human Development Index with Capital Expenditure as an intervening variable. Partially, PAD is influenced of positive on HDI through Capital Expenditure, DAU is influenced of positive on HDI through Capital Expenditure, while DAK is not influenced on HDI through Capital Expenditure.